2003
DOI: 10.1074/jbc.m212576200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of T-type Calcium Channel Gene Expression by Chronic Hypoxia

Abstract: Cellular responses to hypoxia can be acute or chronic. Acute responses mainly depend on oxygen-sensitive ion channels, whereas chronic responses rely on the hypoxia-inducible transcription factors (HIFs), which upregulate the expression of enzymes, transporters, and growth factors. It is unknown whether the expression of genes coding for ion channels is also influenced by hypoxia. We report here that the ␣ 1H gene of T-type voltage-gated calcium channels is highly induced by lowering oxygen tension in PC12 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 60 publications
(86 reference statements)
7
62
0
Order By: Relevance
“…Altogether, these results support the view that reduced expression of the maxi-K ϩ channel ␤ 1 -subunit contributes to vascular pathophysiology in hypoxia. However, it is important to keep in mind that we have studied downregulation of the maxi-K ϩ channel ␤ 1 -subunit within the first 24 to 48 hours of exposure to hypoxia (a protocol normally used for the study of hypoxia-regulated genes [25][26][27] ), whereas the establishment of chronic hypertension in humans results from exposures to hypoxia lasting weeks or months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these results support the view that reduced expression of the maxi-K ϩ channel ␤ 1 -subunit contributes to vascular pathophysiology in hypoxia. However, it is important to keep in mind that we have studied downregulation of the maxi-K ϩ channel ␤ 1 -subunit within the first 24 to 48 hours of exposure to hypoxia (a protocol normally used for the study of hypoxia-regulated genes [25][26][27] ), whereas the establishment of chronic hypertension in humans results from exposures to hypoxia lasting weeks or months.…”
Section: Discussionmentioning
confidence: 99%
“…We assayed the effect of dimethyloxalylglycine (DMOG), a competitive inhibitor of prolyl hydroxylases that stabilizes HIF in normoxia. 5,26,27 DMOG induced HO-1 by approximately 2.5-fold but did not alter the mRNA levels of the ␤ 1 -subunit. However, downregulation of the ␤ 1 -subunit was more pronounced in cells exposed sequentially to hypoxia (6 hours, 1% O 2 ), reoxygenation (18 hours, 20% O 2 ), and hypoxia (6 hours, 1% O 2 ) compared with those exposed to sustained hypoxia (30 hours, 1% O 2 ) (Figure 2).…”
Section: Channel ␤ 1 -Subunit Mrna In Arterial Myocytesmentioning
confidence: 99%
“…Based on the analysis of the rate of mRNA production and stability, these authors concluded that posttranslational mechanisms contribute to the upregulation of the ␤-subunit. Using a clonal cell line (PC12 cells), del Toro et al (2003) examined the effects of chronic hypoxia on T-type Ca 2ϩ channel expression. They observed robust upregulation of the ␣ 1H subunit of the T-type Ca 2ϩ channel and increased current density of this channel in response to prolonged hypoxia.…”
Section: Effects Of Chronic Hypoxia On Sensory Transductionmentioning
confidence: 99%
“…Chronic hypoxia induces a decrease in GLUT1 expression in the adult rat brain but an increase in the fetal as well as in the developing brain (73). Chronic hypoxia also raises the mRNA and channel currents of T-type voltage-gated Ca 2ϩ channels but not of other types of Ca ϩϩ channels in pheochromocytoma-derived PC12 cells (21).…”
Section: Effect Of Hypoxia On the Expression Of Bicarbonate Transportersmentioning
confidence: 99%